FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KANKER SERVIKS - Herniyatun, Herniyatun; Lestyani, Lestyani; Kuntoadi, Gama Bagus; Karlina, Nonok; Dewi, Siti Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Cervical cancer is a malignancy originating from the cervix with abnormal growth of body tissue cells that turn malignant. The number of cervical cancer cases at Arifin Achmad Regional General Hospital Riau Province in 2019 amounted to 312 cases. The purpose of the study was to determine the factors associated with the incidence of cervical cancer at the Arifin Ahmad Regional General Hospital, Riau Province. This study was a cross sectional quantitative analytic study with a sample of 117. Sampling technique with sonsecutive sampling. The instrument in this study used a questionnaire. Data analysis was univariate and bivariate using chi square test. The results of the analysis there is a relationship between knowledge (P=0.000), age (P=0.002), parity (P=0.043), with the incidence of cervical cancer. It is suggested that the Arifin Achmad Hospital of Riau Province be used as further information about the factors associated with the incidence of cervical cancer in patients can be reduced by providing early detection socialization and counseling, especially about risk factors for cervical cancer based on knowledge, age, and parity.Keywords: Cervical Cancer, Parity, Knowledge Age